Economic : - Amacher, Ryan C. (South-Western Pub. Co, 1995)
The microeconomiccs secton of the book begin wiht the basics of supply and demand, using agricultural policy as the primary case study. The policy emphasis continues throughout the micro setion. For example, we cover business choices in response to risk, pulic policy toward monopoly and labor unoins, and the conflict betwen a market-determined income distribution and the demand for polices to alleviate poverty and reduce inequality.